Usulan Sistem Informasi Manajemen Inventory Pembanunan Jalan Tol Cisumdawu Phase 2 Berbasis Digital Business Eco-System (Dbe) Pada Pt. Wijaya Karya - Bagus Mai Prathama; Zeny Fatimah Hunusalela; Mei Lestari (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2021)
Along with the development of industry in Indonesia currently starting towards the industrial revolution 4.0, so the role of technology is needed, especially in the information processing. Data processing, and information precisely, quickly and efficiently are important things that are needed for every company or an agency to increase work productivity, save time and costs. The company's success in maintaining its business is also inseparable from the company's role in managing material inventory so that it can meet production needs as much as possible. This research was conducted at the warehouse department of the Cisumdawu Toll Road Development Project (Cileunyi - Sumedang - Dawuan) Phase 2 Section 2 which is done by PT. Wijaya Karya (Persero) Tbk. The study was conducted for 1 month, starting on August 13, 2019 until September 13, 2019. The results of the development of a Digital Business Eco-System (DBE) based inventory management information system using the System Development Life Cycle (SDLC) method can overcome existing problems namely, can facilitate data collection and data search work required. Based on the calculation results of the USE questionnaire system that has been developed to get an alpha cronbach value of 0.955, it can be concluded that the USE questionnaire has an internal consistency value of Excellent. While the percentage of usability calculation results obtained 88.67%, based on a qualitative scale, the results of the value conversion are